Development of Simulated Remote Monitoring and Operation System under Unstable Electric Power Supply - Satoru Goto; Yoshitaka Matsuda; Takenao Sugi (Journal of ICT Research and Applications, 2020)
In this study, a simulated remote monitoring and operation system was developed for an assumed remote area energy plant in a developing country with few skilled operators and unstable electric power supply. It is useful for skilled operators to be able to monitor and operate the energy system from a remote site. Moreover, low-power equipment is required for the Web server in order to reduce the electric power consumption of the remote monitoring system. The system has the function of remote monitoring of data obtained from sensors through a programmable logic controller (PLC), while the monitoring function is realized by a Web application. The PLC can be operated from a remote monitoring site. The simulated remote monitoring and operation system was constructed using an Internet connection and a virtual private network (VPN) connection. The Internet connection was used for open monitoring of acquired data by the public. The VPN was used for secure remote operation of the device on the plant side from a monitoring PC. The effectiveness of the developed system was conï¬rmed though experiments with a simple simulated plant.